Surgical Management of Malignant Glioma in the Elderly - Klingenschmid, Julia; Krigers, Aleksandrs; Kerschbaumer, Johannes; Thomé, Claudius; Pinggera, Daniel; Freyschlag, Christian F. (Frontiers in Oncology, 2022)
Background: The median age for diagnosis of glioblastoma is 64 years and the incidence rises with increasing age to a peak at 75-84 years. As the total number of high-grade glioma patients is expected to increase with an aging population, neuro-oncological surgery faces new treatment challenges, especially regarding aggressiveness of the surgical approach and extent of resection. In the elderly, aspects like frailty and functional recovery time have to be taken into account before performing surgery. Material & Methods: Patients undergoing surgery for malignant glioma (WHO grade III and IV) at our institution between 2015 and 2020 were compiled in a centralized tumor database and analyzed retrospectively. Karnofsky Performance Scale (KPS) and Clinical Frailty Scale (CFS) were used to determine functional performance pre- and postoperatively. Overall survival (OS) was compared between age groups of 65-69 years, 70-74 years, 75-79 years, 80-84 years and >85 years in view of extent of resection (EOR). Furthermore, we performed a literature evaluation focusing on surgical treatment of newly diagnosed malignant glioma in the elderly. Results: We analyzed 121 patients aged 65 years and above (range 65 to 88, mean 74 years). Mean overall survival (OS) was 10.35 months (SD = 11.38). Of all patients, only a minority (22.3 %) received tumor biopsy instead of gross total resection (GTR, 61.2 %) or subtotal resection (STR, 16.5 %). Postoperatively, 52.9% of patients were treated according to the Stupp protocol. OS differed significantly between extent of resection (EOR) groups (4.0 months after biopsy vs. 8.3 after STR vs. 13.8 after GTR, p < 0.05 and p < 0.001 correspondingly). No significant difference was observed regarding EOR across different age groups. Conclusion: GTR should be the treatment of choice also in elderly patients with malignant glioma as functional outcome and survival after surgery are remarkably better compared to less aggressive treatment. Elderly patients who received GTR of high-grade gliomas survived significantly longer compared to patients who underwent biopsy and STR. Age seems to have little influence on overall survival in selected surgically extensive treated patients, but high preoperative functional performance is mandatory.